Intensive Mothering and Well-being: The Role of Education and Child Care Activity - J. Ignacio Gimenez-Nadal; Almudena Sevilla (Institute for the Study of Labor (IZA), 2016)
The ideology of intensive mothering, whereby mother's time is thought of as crucial for child development, continues to be the dominant cultural framework in the United States. Yet there is little evidence about how mothers differ in their child care experiences from large representative surveys. We use data from the Well-being Module of the American Time Use Survey to understand emotions in mothering experiences, and how these vary by maternal educational attainment and the type of child care activity mothers engage in. We document that, compared to less-educated mothers, higher educated mothers report lower happiness and meaning, and higher levels of fatigue when engaging in mothering activities. The gap in momentary wellbeing among mothers across the educational distribution does not depend on the type of child care activity and suggests that intensive mothering practices are more likely to pressurize the most-educated women, who may subscribe to more time-intensive forms of mothering.
Keywords: J10; 330; mothering; emotional well-being; education gradient; child care; ideology of intensive mothering; time use